Design and Analysis of an Interleaved Totem-Pole PFC Converter for High-Efficiency EV Charging Applications - Dr. S. Parthasarathy; R. Thangasankaran; P. Guru Bathrinath; K. Karthick Raja; S. Jeeva (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Electric Vehicle (EV) charging infrastructure demands high power density, efficiency, and reduced harmonic distortion to meet modern energy standards. This paper presents the design and analysis of an Interleaved Totem-Pole Power Factor Correction (PFC) Converter for high-efficiency EV charging applications. The proposed topology leverages interleaving techniques to reduce input current ripple, enhance power quality, and minimize switching losses, thereby improving overall system efficiency. Simulation results using MATLAB/Simulink validate the performance of the proposed system, achieving high power factor (≈0.99), low Total Harmonic Distortion (THD < 5%), and improved thermal performance. The interleaved control strategy effectively distributes current between multiple phases, leading to reduced electromagnetic interference (EMI) and improved reliability. This study demonstrates that the interleaved totem-pole PFC is a promising solution for next-generation EV fast chargers, offering high efficiency (>95%) and compliance with IEC 61000-3-2 harmonic standards.
Keywords: Power Factor Correction (PFC); Interleaved Totem-Pole Converter; EV Charger; Power Quality; Efficiency; THD Reduction